2018
DOI: 10.1007/s11099-018-0836-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of endogenous ascorbic acid on resistance to high-temperature stress in excised rice leaves

Abstract: Ascorbic acid (Asc) is a major plant antioxidant. L-galactono-1,4-lactone dehydrogenase (GLDH) is an enzyme that catalyzes the last step of Asc biosynthesis in higher plants. Effects of endogenous Asc on resistance to high-temperature stress were studied by using GLDH-overexpressed (GO-2) and GLDH-suppressed transgenic rice (GI-2) as experimental materials. After high-temperature treatment, the maximal quantum yield of PSII was significantly lower in GI-2, and higher in GO-2 compared to wild type rice. The con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Moreover, reduced AC accumulation had a positive correlation with the soil temperatures (r = 0.63, p < 0.05). There is data to suggest that high temperatures induce the synthesis of ascorbate [10,22,23]. Probably, an increase in the AC content in the leaves is a response of the plants to high temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, reduced AC accumulation had a positive correlation with the soil temperatures (r = 0.63, p < 0.05). There is data to suggest that high temperatures induce the synthesis of ascorbate [10,22,23]. Probably, an increase in the AC content in the leaves is a response of the plants to high temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous ascorbic acid protects plants from oxidative stress and maintains the stability of photosynthetic function. Zhang et al [51] studied the effect of endogenous ascorbic acid content by using transgenic rice with overexpressed and suppressed GLDH (L-galactono-1,4,-lactone dehydrogenase) enzyme activity under high temperature. Higher ROS were found in transgenic rice with suppressed GLDH.…”
Section: Induction Of Acclimation By Using Growth Regulators/protementioning
confidence: 99%
“…Under high temperature the level of auxin reduced and reduction of IAA and GAs was more in heat susceptible cultivar than tolerant genotype [56]. Zhang et al [51] studied the effect of spraying auxin on the elongation of pollen tubes of heat-tolerant and susceptible genotypes. They reported that spraying naphthaleneacetic acid reduced and reversed the spikelet sterility of both the heat susceptible and tolerant genotypes of rice by inhibiting the reduction of pollen tube growth.…”
Section: Induction Of Acclimation By Using Growth Regulators/protementioning
confidence: 99%
“…Chl and carotenoids (Car) are two major pigments involved in photosynthesis in the leaves of higher plants (Rodríguez et al 2016, Zhang et al 2018. A decline of the pigment contents is usually regarded as a reliable index of leaf senescence (Zhang et al 2019, Zheng et al 2019.…”
Section: Introductionmentioning
confidence: 99%